2012
DOI: 10.1144/sp371.13
|View full text |Cite
|
Sign up to set email alerts
|

Rock magnetic characterization of early and late diagenesis in a stratigraphic well from the Llanos foreland basin (Eastern Colombia)

Abstract: We have carried out rock magnetic characterizations of different lithofacies along the stratigraphic well Saltarín 1A, in order to learn about the various diagenetic events that could have affected the Miocene sequence of the Llanos foreland basin (Colombia). Thermomagnetic and low-temperature susceptibility measurements performed on some selected samples were complemented with analyses of Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) and isothermal remanent magnetization (IRM) acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…G3 shows evidence for subaerial exposure (i.e., light-colored mudstones and ferruginous nodules), contrasting with the floodplains sequence displayed by G4 with signs of little subaerial exposure (i.e., preservation of coal beds and laminated mudstones). The average volume of shales for these four units is about 50% (Costanzo-Álvarez et al, 2012). On top of G4 lies G5 (81.6-205.5 m), a feldspar and lithic rich sequence of immature sandstones with average volumes of shales of about 20% (Costanzo-Álvarez et al, 2012), that was interpreted as the filling of fluvial channels.…”
Section: Oil Well Saltarin 1a-eastern Llanos Basin Colombiamentioning
confidence: 98%
See 2 more Smart Citations
“…G3 shows evidence for subaerial exposure (i.e., light-colored mudstones and ferruginous nodules), contrasting with the floodplains sequence displayed by G4 with signs of little subaerial exposure (i.e., preservation of coal beds and laminated mudstones). The average volume of shales for these four units is about 50% (Costanzo-Álvarez et al, 2012). On top of G4 lies G5 (81.6-205.5 m), a feldspar and lithic rich sequence of immature sandstones with average volumes of shales of about 20% (Costanzo-Álvarez et al, 2012), that was interpreted as the filling of fluvial channels.…”
Section: Oil Well Saltarin 1a-eastern Llanos Basin Colombiamentioning
confidence: 98%
“…The lowest geological unit reached by this well, at depths between 546.9 and 608.2 m, is part of the Upper Carbonera Formation (i.e., reservoir rock), encompassing a sequence of fluvial-deltaic sandstones. The seal of the reservoir is the Leon Formation that overlies Carbonera (441.8-546.9 m), with a fraction of shales of circa 80% (Costanzo-Álvarez et al, 2012). The Leon Formation is a homogeneous green-colored muddy sequence of freshwater lacustrine sediments.…”
Section: Oil Well Saltarin 1a-eastern Llanos Basin Colombiamentioning
confidence: 99%
See 1 more Smart Citation
“…One of such criteria is the experimentally revealed change in the magnetization of rocks on the paths of hydrocarbons [Оrlyuk, 1999]. Such changes were studied on rock samples in different regions of the world, particularly in China [Liu, et al, 2006], Colombia [Costanzo-Álvarez, et al, 2012], Venezuela [Aldana, et al, 2003], United Kingdom [Abubakar et al, 2015], and other countries. Experimental studies revealed elevated values of magnetic susceptibility and remnent magnetization of sedimentary rocks (syderites, argillites, sandstones, limestones) from hydrocarbon deposits.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2006). Costanzo-Álvarez et al (2012) characterized different lithofacies along the stratigraphic well Saltarín 1A, in order to shed light on the various diagenetic events that could have affected the Miocene sequence of the Llanos foreland basin (Colombia). Direct signal analysis (DSA) of the isothermal remenent magnetization (IRM) acquisition curves was used to determine the relative concentrations for the identified magnetic mineral assemblages at each of the depth levels analyzed.…”
Section: Introductionmentioning
confidence: 99%